Pendampingan dalam Meningkatkan Manajemen Pemasaran Umkm Teh Sari Klaras Pataoh di Desa Nogosaren - Defiani, Siti; Adillah, Farah (Najah: Journal of Research and Community Service, 2026)
Functional drinks can be made from various kinds of plants, one of the plants that can be processed into functional tea drinks is dried banana leaves (klaras). Indonesian people often use fresh and dry banana leaves as food packaging materials. Dried banana leaves give a distinctive aroma, besides that they are used as handicrafts, decorations in traditional ceremonies, can be used as medicine, such as reducing body temperature, and as a natural dye for traditional food. laras tends to go unused. In general, Klaras just throws it away and is considered as trash. This can have an impact on environmental pollution because there will be more and more environmental waste. Therefore, the utilization of claras leaf waste can be used as a functional drink that can cure various diseases